Qualidade da madeira de árvores de eucalipto atacadas por Leptocybe invasa, Gonipterus platensis e Thyrinteina arnobia - Bobadilha, Gabrielly dos Santos (2016)
This experiment aimed evaluate to effect of pests attack in dendrometric variables and wood quality of Eucalyptus trees. Were collected attacked wood from Eucalyptus by Leptocybe invasa (Tocantins e Maranhão) and by defoliation insects Gonipterus platensis and Thyrinteina arnobia (São Paulo). The attacked trees by L. invasa had galls formation throughout the treetop, in big size and with emergency spot. Both G. platensis and T. arnobia host trees had a history of complete defoliation, but with loss of apical dominance only to G. platensis. For all attacked trees were evaluated dendrometrics variables, specific gravity of wood, vessel and fibers dimensions, chemical composition of woods and parameters of Kraft Pulping only for attacked trees by L. invasa. The pests attacks results in changes in growth and wood properties. In attacked trees by L. invasa, the attacks sites affected the dendrometrics variables, frequency of vessels, fiber length, radial density profile and ash wood. There was no change in specifc gravity, vessels and fibers of attack trees by L. invasa e G. platensis, only for T. arnobia wood had decrease in thickness of the fiber wall. Among the wood chemical constituents, only the content of pentosans and ash wood has changed due to pest attacks. The L. invasa attack has caused changes of all parameters of Kraft Pulping.